2022
DOI: 10.3390/jpm12030359
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Center Study for the Development of the Taiwan Cognition Questionnaire (TCQ) in Major Depressive Disorder

Abstract: Cognitive dysfunction is associated with functional impairment of patients with Major Depressive Disorder (MDD). The goals were to explore the associated factors of cognitive impairment in MDD and to develop and validate a brief and culture-relevant questionnaire, the Taiwan Cognition Questionnaire (TCQ), among patients with MDD. This was a cross-sectional, multi-center observational study of MDD patients in Taiwan. Participants of Group 1 from 10 centers contributed to the validation of the TCQ by their respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Clinicians must consider cognitive impairment alongside mood symptoms to ensure functional recovery from the MDD, especially first-episode, drug-naïve (FED) patients. 9,10 Previous studies have revealed that this persistent and clinically significant functional damage may exist in part due to biomechanisms of brain functional connectivity, such as changes in the left dorsolateral cortex, anterior cingulate cortex activation, left hippocampus and orbitofrontal cortex as observed in resting-state functional magnetic resonance imaging (rsfMRI). [11][12][13] These areas support changes of cognitive processes in unmedicated or first-onset MDD.…”
Section: Introductionmentioning
confidence: 99%
“…Clinicians must consider cognitive impairment alongside mood symptoms to ensure functional recovery from the MDD, especially first-episode, drug-naïve (FED) patients. 9,10 Previous studies have revealed that this persistent and clinically significant functional damage may exist in part due to biomechanisms of brain functional connectivity, such as changes in the left dorsolateral cortex, anterior cingulate cortex activation, left hippocampus and orbitofrontal cortex as observed in resting-state functional magnetic resonance imaging (rsfMRI). [11][12][13] These areas support changes of cognitive processes in unmedicated or first-onset MDD.…”
Section: Introductionmentioning
confidence: 99%